2012
DOI: 10.1186/1471-2334-12-221
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the prevention of perinatal transmission of hepatitis B virus between recommendations and routine practices in a highly endemic region: a provincial population-based study in China

Abstract: BackgroundHepatitis B virus (HBV) infection is endemic in China; perinatal transmission is the main source of chronic HBV infection. Simultaneous administration of hepatitis B immune globulin (HBIG) and hepatitis B vaccine is highly effective to prevent perinatal transmission of HBV; however, the effectiveness also depends on full adherence to the recommended protocols in daily practice. In the present investigation, we aimed to identify gaps in immunoprophylaxis of perinatal transmission of HBV between recomm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 21 publications
0
37
0
Order By: Relevance
“…The substantial gaps in the immunoprophylaxis of the infants between the recommendations and routine practices were attributable to the unavailability of HBIG, incomplete knowledge on the prophylaxis of the health care providers, and low prenatal HBsAg screening rate, particularly in rural areas [20]. Additionally, we observed that the children who received HBIG had a lower rate of chronic infection than those who did not receive HBIG (1.7% vs. 3.1%).…”
Section: Discussionmentioning
confidence: 71%
“…The substantial gaps in the immunoprophylaxis of the infants between the recommendations and routine practices were attributable to the unavailability of HBIG, incomplete knowledge on the prophylaxis of the health care providers, and low prenatal HBsAg screening rate, particularly in rural areas [20]. Additionally, we observed that the children who received HBIG had a lower rate of chronic infection than those who did not receive HBIG (1.7% vs. 3.1%).…”
Section: Discussionmentioning
confidence: 71%
“…The three children who had HBsAg carriage may therefore have had mothers who were also carriers. The main challenge here is to ensure that protocols developed for pregnant women who are HBsAg carriers are adhered to 13 , and the universal screening of pregnant women for HBsAg should be aggressively pursued and vaccination of all infants at birth considered. 32 There is also the possibility that these children may have been infected within the first 6 months of life as documented in Senegal.…”
Section: Discussionmentioning
confidence: 99%
“…Such gaps may lead to reduced adherence to protocols that provide maximum efficiency and will in such instances reduce the frequency of seroprotection. 13 A systematic approach to the evaluation of ongoing infant HBV vaccination programmes will ensure that maximum benefits are derived. This is emphasized by the findings that infants in Cameroon did not respond well to the same HBV vaccination regimen as compared to those in the Gambia 6 , and also that genetic factors may account for non-response.…”
Section: Introductionmentioning
confidence: 99%
“…The untimely use of first dose vaccine and the low rate of HBIG administration indicated that there are considerable gaps in the immunoprophylaxis against hepatitis B between the national recommendations and routine practices in China [20]. Therefore, more measures should be taken in the future to achieve full adherence to the recommended prophylaxis in preventing mother-to-child transmission of HBV.…”
Section: Discussionmentioning
confidence: 99%